Emigration and immigration in Portugal - Carvalho, J. (The Oxford handbook of Portuguese politics, 2022)
Portugal has a long history of emigration dating back to the fifteenth century, with large-scale immigration having only developed by the late twentieth century. Within the European context, Portugal shows the second highest rate of emigrants in proportion to the resident population. By contrast, the immigrant population legally settled in Portugal only surpassed half a million individuals in the late 2010s. This chapter presents a historical overview of Portuguese waves of emigration and the public policies that have supported this social phenomenon. Against a background of low attractivity for inflows, the chapter will also assess the waves of immigration, the policies related to immigration control and immigrant integration, and the levels of politicization of this social phenomenon. In short, this investigation will highlight the interdependence between Portugal’s net migration and its positioning as a semi-peripheral country in the world economy.